Early-life infections and life course health and disease in the EU child cohort network - Marianna Karachaliou; Manolis Kogevinas; George Davey Smith; Anne-Marie Nybo Andersen; Demetris Avraam; Henrique Barros; Sunil Bhopal; Nicklas Brustad; Mariona Bustamante; Klaus Bønnelykke; Marie-Aline Charles; Payam Dadvand; et al. (European Journal of Epidemiology, 2026)
Abstract Research into the developmental origins of, and lifecourse influences on, health and disease has a significant gap: infections. Clinical and subclinical infections are nearly universal in early life and can induce structural and functional changes in developing organ systems with life-long consequences. Emerging evidence links common childhood infections—such as Epstein–Barr virus , Cytomegalovirus and Helicobacter pylori —to so-called non-communicable diseases ranging from respiratory to neurodevelopmental and cardiometabolic diseases. Identifying infectious determinants of non-communicable diseases offers substantial opportunities for prevention and early intervention. We describe a newly developed infectious data resource within the EU Child Cohort Network, designed to enable triangulation of evidence on the impact of early life infections on children’s health and long-term trajectories of disease. The network established in 2017, currently brings together 37 pregnancy and childhood cohorts from 16 predominantly European countries and follows over 300,000 children and their families from pregnancy through childhood and, in many cohorts, into adulthood. Cohorts include a comprehensive set of harmonized variables covering health and disease phenotypes (cardiometabolic, respiratory, and mental) that are also well-established early indicators of later-life non-communicable disease risk. Building upon this, we present here the extensive infections data available in the cohorts ranging from questionnaires and registries to serological measurements for more than 20 pathogens. Harmonizing and integrating infection data within the EU Child Cohort Network supports a shift from viewing infections solely as causes of acute disease towards recognising them as integral components of the early-life exposome and potential determinants of lifelong health trajectories.